Contemporary Reflection on Participation as an Essential Dimension of Philosophy of Education in the Context of The Acting Person - Dancák, Pavol (Philosophy and Canon Law, 2021)
This article considers the problem of the idea of participation as an essential dimension of philosophy of education in the context of Karol Wojtyła’s teachings. It proceeds through the concepts of the person and participation. The paper reflects the need for discussion on philosophy of education due to the treatment of individual freedom in an extremely individualistic way. Wojtyła draws on the philosophies of consciousness and the philosophies of being in order to consider the constitution of our ideas in a manner relevant to the education for being together with all people and creatures, with the universe, with the whole world which gives us our own place.